2010
DOI: 10.1007/s10875-010-9464-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-16 as a Marker of Sézary Syndrome Onset and Stage

Abstract: Introduction Sézary Syndrome is one of the most common forms of CTCL. It is characterized by skin infiltration of malignant T-cells. We examined Interleukin-16, a potent T-cell chemoattractant and cell-cycle regulator, as a prospective marker of disease onset and stage. Methods The correlation of total intracellular Interleukin-16 and surface CD26 was studied by flow cytometry. Confocal microscopy was performed to determine localization of Interleukin-16 at different stages of the disease. The levels of Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
1
15
0
2
Order By: Relevance
“…Further, quantification of the interaction between pro-IL-16 and HSC70 by densitometric analysis indicated a direct relationship between the levels of nuclear pro-IL-16 (shown in Figure 4) and HSC70 binding. To further confirm this finding and to address whether the loss of HSC70 binding to pro-IL-16 was limited to those cells classified as tumor cells, 2 additional patients (stage IV) were recruited, and their CD4 + T cells were sorted based on presence or loss of CD26 expression where tumor cells have been characterized as CD26 - (30,39). For these studies, the reverse protocol was used, whereby anti-HSC70 antibody was used for immunoprecipitation and pro-IL-16 was probed on the Western blot.…”
Section: Loss Of Hsc70 Binding To Pro-il-16 In Advanced Ctcl T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, quantification of the interaction between pro-IL-16 and HSC70 by densitometric analysis indicated a direct relationship between the levels of nuclear pro-IL-16 (shown in Figure 4) and HSC70 binding. To further confirm this finding and to address whether the loss of HSC70 binding to pro-IL-16 was limited to those cells classified as tumor cells, 2 additional patients (stage IV) were recruited, and their CD4 + T cells were sorted based on presence or loss of CD26 expression where tumor cells have been characterized as CD26 - (30,39). For these studies, the reverse protocol was used, whereby anti-HSC70 antibody was used for immunoprecipitation and pro-IL-16 was probed on the Western blot.…”
Section: Loss Of Hsc70 Binding To Pro-il-16 In Advanced Ctcl T Cellsmentioning
confidence: 99%
“…Furthermore, the magnitude of increase for IL-16 correlated with disease severity. Protein expression was evaluated by immunohistochemistry analysis and also shown to correlate with disease progression, and, recently, it has been shown that serum IL-16 levels may represent a biomarker for disease severity (30). Assessment of IL-16 protein levels was determined using antibodies targeting the IL-16 C-terminal domain, and, therefore, the regulatory function of pro-IL 16, Skp2, and p27Kip1 in this group of patients was not explored.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear presence of pro-IL-16 prevents Skp2 translation, allowing for elevated expression levels of p27Kip1 and subsequently T-cell quiescence (Carrano et al 1999). Loss of nuclear pro-IL-16 therefore prevents HDAC-3 association with the Skp2 promoter, resulting in elevated Skp2 levels, lower p27Kip1 levels and cell cycle progression (Center et al 2004 We have demonstrated that primary lymphomas from Sézary Syndrome patients exhibit loss of nuclear pro-IL-16 that correlates with increasing stage of disease (Richmond et al 2011). In addition, we have reported that many human T-cell leukemia and lymphoma lines lack the IL-16 gene; however, their in vitro growth is arrested when transfected to express pro-IL-16 (Center et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Badania przeprowadzone przez Richmond i wsp. sugerują, że również w zespole Sezary'ego występuje ścisły związek między stężeniem IL-16 a infiltracją skóry przez limfocyty T CD4+ [41]. U chorych dochodzi do wzrostu stężenia tej cytokiny w surowicy wraz z nasileniem procesu chorobowego.…”
Section: Chłoniak T-komórkowy Skóryunclassified
“…U chorych dochodzi do wzrostu stężenia tej cytokiny w surowicy wraz z nasileniem procesu chorobowego. Korelacja jest na tyle znamienna, że niektórzy autorzy sugerują oznaczanie IL-16 w surowicy jako potencjalnego markera diagnostycznego zespołu Sezary'ego [41]. W pra-widłowych limfocytach T ekspresja fragmentu N-końcowego pre-IL-16 jest obecna zarówno w cytoplazmie, jak i w jądrze komórkowym.…”
Section: Chłoniak T-komórkowy Skóryunclassified